GENDER CONTENT ANALYSIS IN INSTAGRAM SOCIAL MEDIA DISCOURSE @INDONESIAFEMINIS - Hadisaputra, Hadisaputra; Dani, Rahma; Patto, Muhammad Sarfito; Zulkarnain, Iskar; Nurharisha, Siti; Patty, Nayla Ainun Rezkiya; Nur, Andi Asywid (JURNAL SOCIUS, 2025)
Social media has become an integral part of everyday life, allowing users to share information, shape public opinion, and build social narratives. Instagram, as one of the popular platforms in Indonesia, plays a significant role in gender discourse. This study analyzes how the Instagram account @indonesiafeminis constructs gender narratives and audience responses to the issues raised, such as women's empowerment, gender equality. Using a qualitative approach and content analysis, this study explores the account's communication strategies, including the use of infographics, personal narratives, and interactive dialogues. The results show that @indonesiafeminis has succeeded in building inclusive opinions by utilizing Instagram's features to convey strong and inclusive messages. The account also functions as a gender education space, although its success is highly dependent on the delivery of culturally relevant messages. Thus, this study highlights the potential of social media as an inclusive dialogue space that drives social change. However, a more adaptive approach is needed to bridge differences in views and improve gender literacy in society. This study makes an important contribution to understanding the dynamics of gender conversations on Indonesian social media and suggests more effective advocacy strategies.